Measurement of testosterone: how important is a morning blood draw?. (3rd October 2015) - Crawford, E. David; Poage, Wendy; Nyhuis, Allen; Price, David A.; Dowsett, Sherie A.; Gelwicks, Steven; Muram, David
Abstract: Objective: Since testosterone levels exhibit a circadian variation with peak levels in the morning, evidence-based guidelines recommend measuring morning total testosterone (TT) levels as the initial diagnostic test for androgen deficiency. However, it has been suggested that morning blood draw may not be necessary in older men due to a blunted circadian rhythm. We sought to determine whether it is possible to expand the morning sampling window for measurement of TT. Research Design and Methods: TT levels were measured in a subset of men (mean age of 61 years) participating in the 2013 Prostate Cancer Awareness Week. Results: TT levels measured in blood drawn from 8 to 11 AM ( n  = 229) differed significantly from those drawn outside this window ( n  = 442) (411.7 vs 368.3 ng/dl; p  = 0.0003). Differences in TT levels were evident across five blood draw time windows ( p  = < 0.0001) and persisted after adjustment for age and BMI. TT levels in blood drawn from 2 to 5 PM (344.3 ng/dl) and 5 to 8 PM (334.4 ng/dl) differed significantly from that drawn from 8 to 11 AM ( p  < 0.05), while TT levels from 11 AM to 2 PM (396.5 ng/dl) and 8 PM to 8 AM (373.4 ng/dl) did not ( p  = 0.90 and 0.73, respectively). Conclusion: Based on these findings, it may be possible to expand the blood draw time window for measurement of serum TT. This community-based study was not prospectively design to determine the most appropriate blood draw window for TT measurement. Only a single TT measurement was made without consideration for day-to-day variability, and TT levels were not measured in the same men at different blood draw times.